(untitled) (Architecture Image Studies, 2025)
Adobe is one of the oldest building material dating back to the beginning of civilization. It is said that the first use of adobe was around 8-10 thousand BC. Early human beings discovered the origin of adobe. When they saw the soil that was cooked and hardened from the clay next to their hearths, they understood that they could use this tool in building materials. Today, mudbrick is used in all historical buildings, including temples and mosques, on the facades of buildings and in the flooring of structures. Another application of adobe in historical buildings, which one can see as an architectural heritage today, is wind towers. Wind towers are traditional structures used in Iranian architecture in hot, humid, hot and dry climates, and they are tools that refresh and cool indoor air using renewable wind energy. These structures consist of two parts, external and internal. The exterior consists of a closed roof made of adobe and brick on the roof of the building, with most of it a vertical duct at right angles. Wind- towers are usually designed according to the needs of the house/building, so the larger the inlet, the greater the incoming air volume. Wind towers have holes at the top that allows directly the wind inward. The interior of the building consists of a single opening and is divided into two or eight parts with inclined separator wings according to the openings made of mud brick and brick in other types.